2009
DOI: 10.3354/meps08018
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of critical swimming speed of wild-caught and laboratory-reared red drum Sciaenops ocellatus larvae

Abstract: Critical swimming speed (U crit ) provides a useful estimate of maximum swimming performance for fish larvae that can be used to assess transport and migratory potential. We measured U crit of red drum Sciaenops ocellatus larvae through its ontogeny and compared the swimming performance of laboratory-reared larvae to that of wild-caught individuals. U crit increased with ontogeny (size), even though variability in U crit at any ontogenetic state was large. U crit for wild-caught larvae increased from 9.7 to 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 56 publications
4
43
1
Order By: Relevance
“…Dudley et al, 2000;Guan et al, 2008), reporting an improvement in swimming performance until metamorphosis, after which improvements became slower. In disagreement with other studies Leis et al, 2006aLeis et al, ,b, 2007Leis et al, , 2009aFaria et al, 2009), we found no significant relationship between critical speed and size in any of the feeding treatments. This can be attributed to the small size range of tested larvae, or may be merely indicative of the poor swimming capacities of S. senegalensis larvae.…”
Section: Effect Of Starvation On Critical Speedcontrasting
confidence: 57%
See 2 more Smart Citations
“…Dudley et al, 2000;Guan et al, 2008), reporting an improvement in swimming performance until metamorphosis, after which improvements became slower. In disagreement with other studies Leis et al, 2006aLeis et al, ,b, 2007Leis et al, , 2009aFaria et al, 2009), we found no significant relationship between critical speed and size in any of the feeding treatments. This can be attributed to the small size range of tested larvae, or may be merely indicative of the poor swimming capacities of S. senegalensis larvae.…”
Section: Effect Of Starvation On Critical Speedcontrasting
confidence: 57%
“…In order to determine the potential importance of swimming behaviour, it is fundamental to know how these abilities change during ontogeny (e.g. Leis et al, 2009a,b;Faria et al, 2009). In the present study, a significant decrease in swimming abilities of post-flexion larvae was observed in the three feeding treatments, which implies an ontogeny-related effect.…”
Section: Effect Of Starvation On Critical Speedmentioning
confidence: 47%
See 1 more Smart Citation
“…The maximum flow speed was 20 cm s -1 . For details on the swimming chamber characteristics see Faria et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Water velocities at the WCS slots were too low (<0.2 m/s) to limit the migration of most nekton and only exceeded the swimming capabilities of larvae and small (e.g., <3 cm) juveniles (e.g., Mitchell 1989;Luckenbach and Orth 1992;Faria et al 2009). Individuals migrating out of managed marshes have been reported to be larger than those leaving unmanaged marshes (e.g., penaeid shrimps; Knudsen et al 1989Knudsen et al , 1996, ostensibly due to emigration impedance (resulting in long retention times), reduced predation, or decreased competition in managed marshes (Hoese and Konikoff 1995).…”
Section: Discussionmentioning
confidence: 99%